Sageretia thea (Osbeck.) modulated biosynthesis of NiO nanoparticles and their in vitro pharmacognostic, antioxidant and cytotoxic potential. (19th May 2018) - Khalil, Ali Talha; Ovais, Muhammad; Ullah, Ikram; Ali, Muhammad; Shinwari, Zabta Khan; Hassan, Dilawar; Maaza, Malik
Abstract: NiO nanoparticles are biosynthesized using Sageretia thea (Osbeck.) aqueous leave extracts and their biological activities are reported. Nanoparticles (∼18 nm) were characterized through XRD, ATR-FTIR, EDS, SAED, HR-SEM/TEM and Raman spectroscopy. Antibacterial activity was investigated against six pathogenic bacterial strains (gram positive and gram negative) and their corresponding minimum inhibitory concentrations (MICs) were calculated. UV-exposed nanoparticles were investigated to have reduced MICs relative to the NiO nanoparticles have not been exposed to UV. Moderate linear fungal growth inhibition was observed while Mucor racemosus (percentage inhibition 64% ± 2.30) was found to be most susceptible. Cytotoxicity was confirmed using brine shrimps lethality assay (IC50 42.60 μg/ml). MTT cytotoxicity was performed against Leishmania tropica -KWH23 promastigotes and amastigotes revealed significant percentage inhibition across the applied concentrations. IC50 values were calculated as 24.13 μg/ml and 26.74 μg/ml for the promastigote and amastigote cultures of Leishmania tropica . NiO nanoparticles were found. Moderate, antioxidant potential was concluded through assays like DPPH, TAP and TAC. Furthermore, protein kinase inhibition and alpha amylase inhibition is also reported. Graphical Abstract: